Pandemic India: Coronavirus and the Uses of History - Arnold, David (The Journal of Asian studies, 2020)
The onset of the COVID-19 pandemic has produced two different narratives in India. One, here described as “historical,” looks back to the pandemics of the colonial past—bubonic plague from 1896, influenza in 1918–19—as a source of comparisons, lessons, and dire warnings for the present. This narrative envisages the reenactment of past scenes, including flight from the cities, victimization of the poor, and the questioning of state authority. The other narrative, here called “insurgent,” questions the value of historical analogies, doubts that history ever substantially repeats itself, and stresses the specificity of postcolonial Indian politics and health. While recognizing the validity of both narratives, the author urges caution in employing colonial history to critique contemporary events and, while recognizing the 1890s plague as a watershed moment, questions whether even the most devastating pandemics (such as 1918's influenza) necessarily result in profound social, political, and health care changes.